(3ofbhd ef HYV GdQSGFd aj GdLYGdIs
(3ChdgG (B:s
(3bGd hGeG bhdg hefgG EHWGdI GdLYGdI Ydi GdML agPg eSCdI ajgG GNJdGa Hjf GdYdeGA s
(3BNQgG (B:s
(3hbhdg(B: " (3bd GOYh Gddg hGOYh GdQMef jGekG eG JOYhG adg GdCSeGA GdMSfi(B" (3JeJ hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B22s
(3GdfSNI HgG MhGTs
(3hQOJ CjVkG JMJ Qbe (B21/430s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(D 404) s
Keywords: (3GdJhMjO hGdedd hGdfMds